Mapeamento e validação de QTLs para isoflavonas em linhagens endogâmicas recombinantes de soja - Senra, João Felipe de Brites (2013)
Brazil is a major world producer of soybeans, its cultivation being well distributed throughout the country. The culture is characterized by the potential for production of isoflavones, phytoestrogens naturally occurring in plants and chemical structure c